Illegal Maneuver Effect on Traffic Operations at Signalized Intersections: An Observational Simulation-Based Before-After Study Using Response Surface Methodology - Mahdi Jahangard; Mahyar Madarshahian; Hadi Sabur; Reza Rezvani; Abolfazl Mohammadzadeh Moghaddam; Nathan Huynh (Journal of Advanced Transportation)
This study investigates three illegal maneuvers at signalized intersections: pedestrians jaywalking at signalized crosswalks (JSC), vehicles stopping near the intersections (SNI), and vehicles occupying the through lane instead of the left-turn lane to make a left turn (OTL). Traffic microsimulation models of four intersections were developed using Aimsun, and data were collected by a drone over a 3-hour period. The car-following model (Gibbs model) implemented in Aimsun was calibrated for each of the intersections and validated at the 95% confidence level. The validated Aimsun models were used to perform 13 experiments designed to investigate the interaction effects of decreasing two or more illegal maneuvers on travel time and fuel consumption. These 13 experiments were identified using the design of experiments D-optimality criterion. To investigate the main and interaction effects of decreasing two or more illegal maneuvers on travel time and fuel consumption, the response surface methodology (RSM) was used. Using RSM, the statistical model that was found to best fit the simulation results was a quadratic form. The results showed that the dependent variables “travel time ratio” and “fuel consumption ratio” are affected not only by a decrease in violations ratio but also by the volume of traffic as the exogenous variable. It was found that decreasing two of the violations, namely, JSC and SNI, improves travel time and fuel consumption but decreasing OTL has the opposite effect, resulting from the inadequate design of left-turning lane length/capacity and/or inadequate signal timing to accommodate left-turning volume.